Penyelesaian Sengketa di Pengadilan Tata Usaha Negara Semarang Melalui Penerapan E-Court - Muhammad, Irham Ghani; Dwi Kurniawan, Itok (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
This legal research aims to determine the application of E-Court in dispute resolution in the Semarang state administrative court and to find out what obstacles are encountered in the application of E-Court both in court in general and in the Semarang state administrative court. This research belongs to the type of empirical legal research that aims to analyze the law which is seen as patterned community behavior in people's lives who always interact and relate to social aspects. Where in this study is used to analyze the process of implementing E-Court in dispute resolution at the Semarang State Administrative Court. According According to this research, it is known that the Semarang State Administrative Court has provided E-Court services fully effectively starting from registration, litigation, to reading the verdict. The implementation of E-Court in the Semarang state administrative court has a very significant impact on the court process, which includes encouraging high mobility and increasing the productivity level of case handling so that it can realize the realization of an effective and efficient court based on the principles of simple, fast, and low-cost justice.